PENENTUAN KADAR LOGAM BERAT TIMBAL (Pb) DAN Kadmium (Cd) PADA KERANG BULU (Anadara antiquata) DI PERAIRAN SEDANAU KABUPATEN NATUNA (DETERMINATION OF LEVELS OF HEAVY METALS Lead (Pb) AND Cadmium (Cd) IN BULU SHELLS (Anadara antiquata) IN SANDANA WATERS, NATUNA REGENCY) - Samira Samira; Warsidah Warsidah; Dwi Imam Prayitno (Tanjungpura University, 2022)
The waters of Sedanau, Natuna Regency are congested with traffic activities of inter-island transport ships and the construction of docks that have the potential to cause pollution to the aquatic environment. Determination of the levels of heavy metals (Pb) and (Cd) in feather shells (Anadara antiquata) in these waters has been carried out. The purpose of this study was to determine the concentration of heavy metals Pb, Cd in feather shells (Anadara antiquata) which was carried out for 2 time periods, 2020 and 2021 at 2 different sampling stations. Station 1 is close to fishing activities, fishing boat traffic docks and inter-island passenger ships, station 2 is close to fishing boat docks and floating net cages but far from fishing activities and ship traffic. Measurement of the concentration of heavy metals Pb and Cd using the Atomic Absorption Spectrophotometer (SSA) method with reference to the Indonesian National Standard (SNI) Number 06-6992.2-2004 heavy metals Pb and Cd in feather shells (Anadara antiquata). The results of the measurement of heavy metal concentrations of Pb and Cd in feather shells (Anadara antiquata) in the first year were the content of (Cd) at station 1 of 0.0214 g/g, station 2 of 0.0236 g/g and (Pb) of station 1 of 0. 0.0109 g/g, station 2 was not detected, while in the second year the content (Cd) of station 1 was 1.3472 g/g, station 2 was 0.9980 g/g and (Pb) stations 1 and 2 were not detected. heavy metal content. Measurements in the second year of heavy metal content of Pb and Cd were lower than in the first year which had exceeded the threshold allowed in the Indonesian National Standard (SNI) No. 7387 of 2009 concerning the Maximum Limit of Heavy Metal Contamination in Food Lead (Pb) 1.5 mg/kg and Cadmium (Cd) 1.0 mg/kg